STRATEGI PERENCANAAN KONSEP KAMPUNG TERPADU MELALUI POTENSI KOMODITAS PERTANIAN (STUDI KASUS KAMPUNG KWEEL KABUPATEN MERAUKE) - Mega Ayu Yusuf; Petrus Nong Robi; Muhammad Abdul Azis (Faculty of Agriculture, Musamus University, 2022)
Agriculture is one of the important sectors supporting the economy of a region, but its contribution tends to decrease every year. In order to support agricultural development, especially in villages, the government applies the concept of regional development with an integrated village approach. This concept can be implemented by knowing the potential and competitiveness of agricultural commodities and conditions in the field. Thus, this study aims to identify the potential and level of competitiveness of superior agricultural commodities and to formulate an integrated village-based regional economic development strategy. The analytical method used is the method of LQ analysis, Shift Share and SWOT. The results showed that superior and competitive commodities included sago, taro and sweet potato in the food crops sub-sector, mustard greens and bamboo shoots in the vegetables sub-sector, matoa, pineapple, bananas in the fruits sub-sector. Coconut and cashew in the plantation subsector and snapper, tilapia and snakehead in the fisheries sub-sector. The strategy that can be applied is the aggressive strategy (S-O), which is facilitating the provision of agricultural production facilities as well as increasing training and policy outreach, especially related to the development of integrated villages.